2021
DOI: 10.3390/ph14121216
|View full text |Cite
|
Sign up to set email alerts
|

Computational and In Vitro Experimental Investigations Reveal Anti-Viral Activity of Licorice and Glycyrrhizin against Severe Acute Respiratory Syndrome Coronavirus 2

Abstract: Without effective antivirals, the COVID-19 pandemic will likely continue to substantially affect public health. Medicinal plants and phytochemicals are attractive therapeutic options, particularly those targeting viral proteins essential for replication cycle. Herein, a total 179 phytochemicals of licorice (Glycyrrhiza glabra) were screened and scrutinized against the SARS-CoV-2 main protease (Mpro) with considerable binding affinities in the range of −9.831 to −2.710 kcal/mol. The top 10 compounds with the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In Vero E6 cells, GR fought SARS-CoV-2 by active inhibition of the main protease (Mpro) of SARS-CoV-2 and inhibited SARS-CoV-2 replication (van de Sand et al 2021 ; Gowda et al 2021 ) In another study using computational and experimental investigations in vitro, licorice and GR treatment when used concurrently, post-infection, and pre-treatment have demonstrated potent anti-SARS-CoV-2 ability through two mechanisms of action as SARS-CoV-2 inhibitors for main protease (Mpro) responsible for replication and prevent cell binding mediated by spike protein. The results of this study suggested that GR can be used as a protective agent against COVID-19 (Tolah et al 2021 ). In vivo study on a mouse model of COVID-19 combined with in vitro experiments; GR nanoparticles exert antiviral and anti-inflammatory effects, preventing organ damage and death by prominently suppressing the replication of COVID-19 (Zhao Z et al 2021).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In Vero E6 cells, GR fought SARS-CoV-2 by active inhibition of the main protease (Mpro) of SARS-CoV-2 and inhibited SARS-CoV-2 replication (van de Sand et al 2021 ; Gowda et al 2021 ) In another study using computational and experimental investigations in vitro, licorice and GR treatment when used concurrently, post-infection, and pre-treatment have demonstrated potent anti-SARS-CoV-2 ability through two mechanisms of action as SARS-CoV-2 inhibitors for main protease (Mpro) responsible for replication and prevent cell binding mediated by spike protein. The results of this study suggested that GR can be used as a protective agent against COVID-19 (Tolah et al 2021 ). In vivo study on a mouse model of COVID-19 combined with in vitro experiments; GR nanoparticles exert antiviral and anti-inflammatory effects, preventing organ damage and death by prominently suppressing the replication of COVID-19 (Zhao Z et al 2021).…”
Section: Resultsmentioning
confidence: 84%
“…Glycyrrhizin mitigated viral proteins induced lung cell pyroptosis and activation of macrophages and resolving hyper-inflammatory processes Glycyrrhizin prevents SARS-CoV-2 S1 and Orf3a induced high mobility group box 1 (HMGB1) release and inhibits viral replication Gowda et al ( 2021 )*** Glycyrrhizic acid (GA) nanoparticles (GANPs) In vitro and in vivo studies in mouse model of COVID-19 GANPs and GA exert antiviral and anti-inflammatory effects, relieving organ damage and conferring a significant survival advantage to infected mice GANPs and GA could prominently suppress the proliferation of COVID-19 Zhao et al ( 2021a , b ) Licorice extract and glycyrrhizin Computational and in vitro experimental investigations In vitro studies demonstrated robust anti-SARS-CoV-2 activity of licorice and glycyrrhizin under different treatment protocols (simulations treatment with viral infection, post-infection treatment, and pre-treatment, Multiple mechanisms for action. Inhibitors for SARS-CoV-2 main protease (Mpro) Tolah et al ( 2021 ) Glycyrrhizic acid Experimental in vitro and Docking analysis Glycyrrhizic acid inhibits SARS-CoV-2 infection By blocking spike protein-mediated cell attachment. Molecules Li et al ( 2021 ) Glycyrrhizic acid Comparing with ginsenoside Ra2, ginsenoside Rb3, berberine chloride Combination of computer-aided drug design and in vitro biological verification Glycyrrhizic acid was found to be the most efficient and nontoxic broad-spectrum anti-coronavirus molecule in vitro, especially, the significant effect on SARS-CoV-2 Glycyrrhizic acid performed the best in disrupting the interaction between the RBD of SARS-CoV-2 and ACE2 Yu et al ( 2021 ) Glycyrrhiza glabra extract contains 6.25% of glycyrrhizinic acid Rats in normal or stress condition This study provide evidence that glycyrrhiza glabra extract may reduce an entry point of SARS-CoV-2 Glycyrrhiza glabra root extract leads to a significant reduction in the expression of ACE2 in the small intestine Jezova et al ( 2021 ) Glycy...…”
Section: Resultsmentioning
confidence: 99%
“…Other natural product sources screened by docking and MM/PB­(GB)­SA against Mpro were flavonoid-based phytochemical constituents of calendula officinalis, phytochemicals in Indian ginseng, food compounds, marine natural polyketides, malaria-box compounds, cressa cretica compounds, strychnos nux-vomica products, ayurvedic compounds, moringa oleifera compounds, withania sp. products, stilbenolignans from plants, acridinedione analogs, alkaloids from justicia adhatoda , tea plant products, neem compounds, turmeric compounds, echinacea angustifolia products, Withania somnifera (ashwagandha) products, cyperus rotundus Linn products, salvia plebeia products, lichen compounds, curcuma longa products, and polyphenols from broussonetia papyrifera . …”
Section: Methods and Approachesmentioning
confidence: 99%
“…[29,45] In addition, glycyrrhizin could relieve Covid-19 symptoms with its liver-protective effect and the suppression of airway mucus hypersecretion. [46] Although in silico simulation model is commonly used to evaluate the docking value of newly designed compounds, [47] in vivo and clinical experimental models are still required to confirm the antiviral potential of G. glabra. [47] The pharmacological activities of G. glabra including anti-oxidation, anti-inflammatory, anti-tussive, anticancer, anti-viral, cyto-protection and immunomodulation.…”
Section: Regulation Of Mpro and Cytokine Stormmentioning
confidence: 99%
“…[46] Although in silico simulation model is commonly used to evaluate the docking value of newly designed compounds, [47] in vivo and clinical experimental models are still required to confirm the antiviral potential of G. glabra. [47] The pharmacological activities of G. glabra including anti-oxidation, anti-inflammatory, anti-tussive, anticancer, anti-viral, cyto-protection and immunomodulation. [28,48] The anti-inflammatory action of G. glabra is mainly attributed to its ability to suppress oedema in inflammatory events associated with myocardial and lung diseases.…”
Section: Regulation Of Mpro and Cytokine Stormmentioning
confidence: 99%